2019
DOI: 10.3390/ijerph16122127
|View full text |Cite
|
Sign up to set email alerts
|

A Novel, Individualized Exercise Program for Patients with Peripheral Arterial Disease Recovering from Bypass Surgery

Abstract: The effectiveness of an individual six-month-long physical exercise program in improving health-related quality of life (HRQOL) is unclear. There is some evidence that an individual exercise program can be effective for this aim. The goal of this study was to compare an individual six-month-long physical exercise program for patients with PAD (Peripheral Arterial Disease) with a traditional exercise program and find the effect of these programs on HRQOL and PAD risk factors. The study included patients who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
1
0
1
Order By: Relevance
“…99 Quality of life was assessed by various studies and various tools were used to quantify the results. These tools included Walking Impairment Questionnaire (WIQ), 40,46,48,50,51,62,65,71,72,76,78 Medical Outcomes Study Short Form Health Survey (SF-36), 40,44,45,48,51,55,57,61,62,65,71,78,82,87 Edinburgh Claudication Questionnaire (ECQ), 28 Vascular QoL (VascuQoL) Questionnaire, 44,61,72,82 Health Utilities Index, 46 Intermittent Claudication Questionnaire (ICQ). 51 Self-Efficacy for Physical Activity (SEPA) Questionnaire 72 and European Quality of Life Visual Analog Scale (EQ-VAS).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…99 Quality of life was assessed by various studies and various tools were used to quantify the results. These tools included Walking Impairment Questionnaire (WIQ), 40,46,48,50,51,62,65,71,72,76,78 Medical Outcomes Study Short Form Health Survey (SF-36), 40,44,45,48,51,55,57,61,62,65,71,78,82,87 Edinburgh Claudication Questionnaire (ECQ), 28 Vascular QoL (VascuQoL) Questionnaire, 44,61,72,82 Health Utilities Index, 46 Intermittent Claudication Questionnaire (ICQ). 51 Self-Efficacy for Physical Activity (SEPA) Questionnaire 72 and European Quality of Life Visual Analog Scale (EQ-VAS).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 46 studies included in this review evaluated the effectiveness of physical interventions i.e.,. 31,32,34,37,38,40-42,44-47,49,51,53,55,57-59,61,62,65,66,68-75,77,78,82-84, 87-90,92,93, 98 The majority of trials 34,41,47,51,53,55,62,71,78,83,89,90,92,93 stated the use of SET or simply exercise training to estimate its impact on the PAD or associated/ defined parameters. However, one of the main issues that were noticed that there was no protocol based on which SET or any other exercise interventions was standardized.…”
Section: Physical Interventionsmentioning
confidence: 99%
“…Benefit of a supervised exercise therapy in patients with PAD after revascularization has been previously assessed in some studies which also reported improved walking distance and functional improvement. 17,18 However, these studies focused mostly on supervised exercise therapy (SET) and were not.…”
Section: Discussionmentioning
confidence: 99%
“…TEIXEIRA de LEMOS et al, 2012), em pré-diabéticos(GAITÁN et al, 2019), mulheres na pós-menopausa(BORER et al, 2019), adolescentes com sobrepeso ou pacientes cardíacos (JAKUBSEVIČIENĖ; MĖLINYTĖ;KUBILIUS, 2019). Essa abordagem é significativa para o aumento contínuo de um alto complexo enzimático protetor do corpo ao estresse oxidativo, que influência o aumento da reciclagem de vitaminas (C e E) e da SI(TEIXEIRA de LEMOS et al, 2012).Sobre o grupo etário mais jovem, 3 formas de exercício aplicados em adolescentes com sobrepeso ou obesidade foi possível notar uma contribuição igual à melhoria da SI, gordura hepática e lipídeos nos músculos esqueléticos, bem como na aptidão cardiorrespiratória e no nível de glicemia 2 horas no teste oral de tolerância a glicose (TTOG)(LEE, S et al, 2019).Também foi possível notar em diabéticos que o aumento habitual da prática de exercícios físicos contribui para a melhoria da função microvascular que diminui outros agravos inerentes aos pacientes com hiperglicemia crônica, como o acidente vascular encefálico, doenças renais, retinopatias, neuropatias e declínio cognitivo (demência)(SÖRENSEN et al, 2020).Available from: http://www.pubmedcentral.nih.gov/articlerender.fcgi?artid=4259868&tool=pmcentrez&rend ertype=abstract BARREIRA E, et al Dietary program and physical activity impact on biochemical markers in patients with type 2 diabetes: A systematic review.…”
unclassified